Amartya Sen: The Idea of Justice (Cultura Económica, 2019)
The paper analyzes the importance of Amartya Sen’s last book, The Idea of Justice, as it represents a synthesis of all his thinking. The author points out that the importance of this work lies in its ethical dimension, guided by reason, and compares it to John Rawls’s theory, drawing parallels and differences between the thinking of these intellectuals. Then, Migliore exposes the three great themes analyzed by Sen in his theory: the question of fair distribution of resources, democracy or freedom of participation, and human rights. Finally, as a conclusion, he explains that the work of the Indian economist has interesting coincidences with Christian social thinking.
Keywords: THE IDEA OF JUSTICE; AMARTYA SEN; JOHN RAWLS; DISTRIBUTIVE JUSTICE; FREEDOM; HUMAN RIGHTS